Special issue: Papers from ICEA After the Pandemic Conference Series, fall 2021 - Jerzy D. Konieczny (Review of Economic Analysis (REA), 2022)
Papers in the special issue were presented at five conferences in the After the Pandemic Conference Series, organized by the International Centre for Economic Analysis (ICEA), for which the Review is the official journal, and held online between October 29, 2021 and December 10, 2021. The list of the conferences in the series is at the end of the introduction.
Keywords: G32; H26; I1; I18; I24; J16; J60M14; 330; Happiness; Inequality; Working from Home; Public Health; Gender Inequality; Pandemic; Covid-19